2017
DOI: 10.2174/1871530317666171114121533
|View full text |Cite
|
Sign up to set email alerts
|

Extra Virgin Olive Oil and Cardiovascular Diseases: Benefits for Human Health

Abstract: The studies analyzed demonstrated the role of EVOO as anti-inflammatory, antioxidant and vasodilatory nutrient that may contribute to lower the atherosclerotic burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
75
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 51 publications
(72 reference statements)
1
75
1
5
Order By: Relevance
“…Virgin olive oil, obtained by mechanical and physical methods from fruits of the olive tree ( Olea europaea L.), incorporates a huge chemical richness in terms of bioactive compounds (Boskou, ). Several studies showed that some of these microcomponents play important roles in human health (Huang and Sumpio, ; López‐Miranda et al, ; Nocella et al, ; Visioli and Bernardini, ). Indeed, olive oil consumption has been associated with lower incidence rates of coronary disease and cancer, improved digestive functions, and brain aging delaying, among others (Abuznait et al, ; Huang and Sumpio, ; Nocella et al, ; Psaltopoulou et al, ; Visioli and Bernardini, ).…”
Section: Introductionmentioning
confidence: 99%
“…Virgin olive oil, obtained by mechanical and physical methods from fruits of the olive tree ( Olea europaea L.), incorporates a huge chemical richness in terms of bioactive compounds (Boskou, ). Several studies showed that some of these microcomponents play important roles in human health (Huang and Sumpio, ; López‐Miranda et al, ; Nocella et al, ; Visioli and Bernardini, ). Indeed, olive oil consumption has been associated with lower incidence rates of coronary disease and cancer, improved digestive functions, and brain aging delaying, among others (Abuznait et al, ; Huang and Sumpio, ; Nocella et al, ; Psaltopoulou et al, ; Visioli and Bernardini, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated relationships between the saturation of dietary fat and the concentrations of total plasma cholesterol and higher blood pressure [5], hepatic steatosis [6], adipose chronic inflammation [6], ectopic lipid deposition in the liver and brown fat [6], overweight [6,7], hyperinsulinemia [7], and hepatic insulin resistance [8]. However, high fat diets that are rich in monounsaturated fatty acids exert a protective role [9][10][11][12][13][14][15].High monounsaturated fatty acids diets also have demonstrated an effect on the secretion of the insulinotropic peptide GLP-1 (glucagon-like peptide 1) [16,17]. GLP-1 is an incretin hormone with antidiabetic action that is capable of stimulating insulin secretion [18,19], increasing beta cell neogenesis [20], inhibiting beta cell apoptosis [20], inhibiting glucagon secretion [21], delaying gastric emptying, and inducing satiety [20,21].…”
mentioning
confidence: 99%
“…Several studies have indicated relationships between the saturation of dietary fat and the concentrations of total plasma cholesterol and higher blood pressure [5], hepatic steatosis [6], adipose chronic inflammation [6], ectopic lipid deposition in the liver and brown fat [6], overweight [6,7], hyperinsulinemia [7], and hepatic insulin resistance [8]. However, high fat diets that are rich in monounsaturated fatty acids exert a protective role [9][10][11][12][13][14][15].…”
mentioning
confidence: 99%
“…In recent years, the dietary benefits of omega-3 polyunsaturated fatty acids (ω-3 PUFAs) and oleic acid have been heralded for improving cardiovascular health 31 . Therapeutic intravenous administration of oleic acid or ω-3 PUFAs is not a realistic option due to poor aqueous solubility and propensity to form lipid emboli [49][50] .…”
Section: Ldl-oa-npsmentioning
confidence: 99%